Impact of Early Follow-Up Intervention on Parent-Reported Postconcussion Pediatric Symptoms: A Feasibility Study. Issue 6 (November 2016) - Mortenson, Patricia; Singhal, Ashutosh; Hengel, Alexander R.; Purtzki, Jacqueline
Abstract : Objectives: To investigate the effectiveness and feasibility of early intervention telephone counseling with parents in limiting postconcussion symptoms and impacts on children and youth. Setting: Recruitment occurred postdischarge from one pediatric emergency department. Participants: Sixty-six parents of children aged 5 to 16 years with a diagnosis of a concussion injury. Design: A pilot, randomized controlled study compared the efficacy of telephone counseling (reviewing symptom management and return to activity with parents at 1 week and 1 month postinjury) with usual care (no formalized follow-up). Main Measures: The Post-Concussion Symptom Inventory and the Family Burden of Injury Interview administered with parents by a blinded therapist at 3 months postinjury. Results: No significant difference between the groups at 3 months postinjury in postconcussion symptoms ( P = .67) and family stress ( P = .647). Conclusion: The findings suggest that the early counseling intervention strategy trialed herein may not be effective for children and youth who experience significant postconcussion symptoms. Further research is needed to determine whether more intensive and integrated care would better serve children.